Facilitating Inclusive Global Trade: Evidence from a Field Experiment - Hui, Xiang (Management Science, 2020)
How can we make global trade inclusive for smaller sellers and firms? I present causal evidence that a major e-commerce platform increases on-site exports from small sellers through integrating an existing administrative and logistic service. The export increase comes exclusively from small sellers and exclusively along the extensive margin—that is, from new sellers or new destinations. Furthermore, the export increase is larger for more distant countries and differentiated products. I provide strong evidence that the distribution of export increase is driven by a reduction in export entry cost. I discuss the importance of reducing export entry cost for facilitating inclusive global trade. This paper was accepted by Chris Forman, information systems.